2021
DOI: 10.3389/fncel.2021.661838
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Brain Barrier Dysfunction Amplifies the Development of Neuroinflammation: Understanding of Cellular Events in Brain Microvascular Endothelial Cells for Prevention and Treatment of BBB Dysfunction

Abstract: Neuroinflammation is involved in the onset or progression of various neurodegenerative diseases. Initiation of neuroinflammation is triggered by endogenous substances (damage-associated molecular patterns) and/or exogenous pathogens. Activation of glial cells (microglia and astrocytes) is widely recognized as a hallmark of neuroinflammation and triggers the release of proinflammatory cytokines, leading to neurotoxicity and neuronal dysfunction. Another feature associated with neuroinflammatory diseases is impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
185
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(192 citation statements)
references
References 233 publications
(304 reference statements)
3
185
0
4
Order By: Relevance
“…Conventional photon RT is a therapeutic cornerstone in brain cancer and it is commonly postulated that this treatment modality alters BBB permeability [16] , a key protective component to maintain brain tissue homeostasis. The downside of a dysfunctional BBB is that the brain tissue is more exposed to blood-borne proteins, waste products and pathogens, potentially resulting in a variation of neurological disorders such as neuroinflammatory reactions and neurodegenerative diseases [99] , [100] , [101] . On the other hand, in the context of neurological diseases and brain cancer, an increased BBB permeability can have therapeutic advantages, whereby drugs that normally have limited access to the brain parenchyma are able to better reach the diseased brain [4] .…”
Section: Discussionmentioning
confidence: 99%
“…Conventional photon RT is a therapeutic cornerstone in brain cancer and it is commonly postulated that this treatment modality alters BBB permeability [16] , a key protective component to maintain brain tissue homeostasis. The downside of a dysfunctional BBB is that the brain tissue is more exposed to blood-borne proteins, waste products and pathogens, potentially resulting in a variation of neurological disorders such as neuroinflammatory reactions and neurodegenerative diseases [99] , [100] , [101] . On the other hand, in the context of neurological diseases and brain cancer, an increased BBB permeability can have therapeutic advantages, whereby drugs that normally have limited access to the brain parenchyma are able to better reach the diseased brain [4] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we consider that sAPPα proteins may leak from the BBB. Studies have shown that excess sAPPα can activate microglia and astrocytes ( 30 , 57 ), which contribute to BBB dysfunction ( 66 ), but it is unclear whether the sAPPα protein will leak from the damaged BBB, which needs to be further verified in animal experiments and will be a very valuable direction for our subsequent research. In conclusion, with the limitations of the current sample, we were able to obtain only peripheral blood in the hope of finding early predictive markers; in our next step, we will verify these markers in animal experiments to explore the source of all sAPP proteins.…”
Section: Discussionmentioning
confidence: 99%
“… 39 When the BSCB is damaged, these inflammatory mediators can drive peripheral immune cells to the lesion site; they then polarize towards pro-inflammatory phenotypes and exhibit cytokine expression patterns similar to the resident inflammatory cells, resulting in a more severe local inflammatory response that consequently hinders neurological function recovery ( Figure 1 ). 40 , 41 A sequential inflammatory cascade is switched on following SCI. Neutrophils are driven to the lesion site within 24 hours and facilitate phagocytosis and the removal of cellular debris; many neutrophils also secrete distinct oxidative and tissue-degrading enzymes, proteases, reactive oxygen species (ROS), and tumor necrosis factor (TNF)-α, creating a harmful microenvironment that is neurotoxicity to neurons.…”
Section: Inflammation After Scimentioning
confidence: 99%